Impact of CQI feedback rate/delay on scheduling video streaming services in LTE downlink - Basukala, Riyaj; Mohd. Ramli, Huda Adibah; Sandrasegaran, Kumbesan; Chen, Lu (IEEE, 2010)
The major attraction of the next generation wireless systems such as the third generation partnership project (3GPP) Long Term Evolution (LTE) is the availability of high data-rate video services at high user velocities. However, it is quite a challenge to provide the required level of quality of service (QoS) and maintain the planned system performance due to limited radio resources, unreliable radio propagation channel and high user demands. This paper analyses the impact of channel quality indicator (CQI) delay and its aperiodic reporting rate on the performance of a well known scheduling algorithm serving video streaming users at different velocities. The analysis will be compared against the system having perfect and delayed channel knowledge at each scheduling instance. We then recommend the minimum rate requirement of aperiodic CQI reports to maintain the required QoS for a certain number of video streaming users.